2023
DOI: 10.1371/journal.pone.0287579
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between carbon emissions, energy consumption, and economic growth: Evidence from global economies

Hasara Dissanayake,
Nishitha Perera,
Sajani Abeykoon
et al.

Abstract: Renewable energy holds a remarkable role in clean energy adaptation due to the much lower carbon footprint it releases compared to other fossil fuels. It also has a positive impact by slowing down the rate of climate change. The study has examined the links between renewable and non-renewable energy use, CO2 emissions and economic growth in developed, developing, and LDCs and Economies in Transition between 1990 and 2019 in 152 countries. Granger-causality has been used as the methodology to investigate the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…Based on the analysis findings, it can be inferred that carbon emissions hurt the utilization of clean energy. More specifically, as carbon emissions increase, the adoption of clean energy decreases [ 147 ]. The inverse relationship between environmental sustainability and carbon emissions underscores the intricate dynamics.…”
Section: Discussion Of the Study Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the analysis findings, it can be inferred that carbon emissions hurt the utilization of clean energy. More specifically, as carbon emissions increase, the adoption of clean energy decreases [ 147 ]. The inverse relationship between environmental sustainability and carbon emissions underscores the intricate dynamics.…”
Section: Discussion Of the Study Findingsmentioning
confidence: 99%
“…The importance of developing laws and initiatives to reduce carbon emissions and accelerate the shift to renewable energy sources is emphasized. Efforts to reduce carbon emissions from industrial and transportation sectors can involve encouraging the advancement and implementation of clean energy technology, investing in infrastructure for renewable energy sources, and implementing regulatory measures [ 119 , 147 ].…”
Section: Discussion Of the Study Findingsmentioning
confidence: 99%
“…Most research indicated a negative, mostly U-shaped relationship between renewable energy consumption and CO 2 reduction, whether for Asian countries (Muhammad & Khan, 2019)energy use, CO 2 emissions and capital role in the economic growth. This study applies generalized method of moments (GMM, African (Inglesi-Lotz & Dogan, 2018), OECD (Bilgili et al, 2016), the European Union (Muço et al, 2021), United States (Ali et al, 2020), 150 countries of the world (Cialani, 2017), or all economies (Dissanayake et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the Fifth Plenary Session of the 19th CPC Central Committee, the CPC Central Committee proposed to build a new development pattern with the domestic macro-cycle as the main body and the domestic and international double-cycle promoting each other, which is an opportunity for our country to follow the trend and realize the sustainable development of energy with high quality. China's demand for energy will undoubtedly continue to grow in the context of high-quality economic development, and the stimulation of the economy needs to be accompanied by a focus on actions to reduce carbon dioxide emissions and the development of renewable energy sources [34]. Empirical studies from China have proven that optimizing energy structure [35,36] and energy resource allocation [37] has a positive effect on promoting the high-quality development of China's economy.…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%